NEW TRENDS IN THE EVOLUTION OF VISUAL ARTS INFLUENCED BY MEDIA TECHNOLOGIES / ТЕНДЕНЦИИ РАЗВИТИЯ ВИЗУАЛЬНЫХ ИСКУССТВ ПОД ВЛИЯНИЕМ НОВЫХ ЭКРАННЫХ ТЕХНОЛОГИЙ - STROEVA OLESYA V. / СТРОЕВА О.В.; ARONIN SERGEY V. / АРОНИН С.В. (Наука телевидения)
The evolution and search for new means of expression in the visual arts is currently associated with the direct influence of media technologies. The visual arts have become a subcategory of the media culture which offers the viewer a variety of sophisticated and technically high-quality visual products. The opportunity of creating virtual, immersive and interactive art spaces attracts attention of artists, involved in the collective creativity of art groups, including IT engineers and designers. In terms of their contents, contemporary art projects often represent controversy or dialogue with tradition, developing aesthetics of pop culture and post-humanistic aesthetics. Many works of visual art today present virtual or semi-virtual performances which immerse the viewer in a special environment of images of mixed reality. The main task of modern installations is to create a new experience on the border of the physical and virtual body. Reconsideration of physicality as the antithesis of virtuality is unfolding in the projects of the actively developing trend of bio-art. Contemporary theater is also integrating screen technologies as a new artistic means. The role of the screen in the theater can be either purely technical, facilitating the director’s visualization of the script, or semantically valuable and, to some extent, thought provoking. The latter is more significant for the theatrical process, as it not only carries the potential for the development of technical equipment and stage machinery, but also opens up a new space and means for creativity. The most promising perspectives of the screen and projection usage in the light of synthetic arts and the development of high technologies are foreseen in enhancing their independence. Understanding the screen as an independent artistic feature along with the script, actors, set design, sound solution, the light score may be construed as an integral part of the theatrical language in the future. The authors of the article come to the conclusion that in most contemporary works of the visual arts today, artists record the process of the emergence of a new type of aesthetic perception of the “polyontological era”, where images are collected and generated in a new media dimension, as well as new forms of interaction between the viewer and works of art.